(untitled) (PAAN Journal, 2026)
The concept of governance is not new. It is as old as human history, dating back to the beginning of civilization. The concept entered debates and gained popularity in the 1980s and 1990s, and there was tension between many academics and international practitioners who employ ‘governance’ to suggest a complex set of structures and processes, both public and private, and some popular writers explain it as government or a system of national government. The governance concept has gained impetus in both national and international public policy due to its practical utility for analyzing and solving problems across various contentious issues of public policy at multiple levels, viz., international, national, regional, and subnational. Moreover, the emergence of governance occurred as ‘a response to dissatisfaction and failures with the state-dominated models of economic and social development that existed throughout the socialist bloc and much of the Third World in the 1950s, 1960s, and 1970s’. This paper makes a brief overview of the key concepts of governance with multitude of diverse notions of the term; illustrates the shift from governance to good governance and why the concept emerged as a global agenda in public policy; visualizes how governance can be good or bad; evokes global governance as an integrative term that captures many current transformations in the world politics of governance; and finally concludes with some critical perspectives of governance.